Seguridad eléctrica y peligro de la descarga de arco - Cevallos, K. (2010)
The risk present in any kind on electrical installation could be reduced if a complete analysis of all installation is performed. Generally a short circuit study is performed and good electrical protections are installed. It can clear electrical fault in shorter period of time however at the moment that the fail happens it produces an arc flash that can hurt a worker located in that site. Actually in the electrical security plan a new concept have been introduced which is an electrical arc flash study. Using equations based on experimental results. This allows performing an evaluation of risk in order to know what need to be done in the different types on installation. After this implementation the risk that a Worker or a person is exposed must be reduced.